A multicentered evaluation of the waiting period after PVI guided by the Ablation Index. (14th October 2021) - De Campos, D; Sousa, P; Adao, L; Primo, J; Khoueiry, Z; Lebreiro, A; Fonseca, P; Lagrange, P; Elvas, L; Goncalves, L
Abstract: Background: Since the widespread availability of contact-force sensing catheters the need of a waiting period has not been reassessed in paroxysmal atrial fibrillation (AF) ablation. Objective: The purpose of this study was to evaluate if pulmonary vein isolation (PVI) guided by the Ablation Index (AI) could spare the need for a waiting phase. Methods: This multicentre, prospective, randomized study consecutively recruited patients referred for first-time catheter ablation of symptomatic drug-refractory paroxysmal AF from May 2019 to February 2020. Patients performed PVI tailored to different AI values according to the different left atrium walls (550 for anterior, 500 for roof, 450 for inferior and 400 for posterior). Patients were enrolled in 1:1 ratio to PVI and 20 min of waiting time versus PVI without a waiting period. Acute reconnection (either spontaneous or after adenosine) and 1-year arrhythmia freedom were analyzed. Results: The study included 124 patients (61 in the waiting period group and 63 in the group without the waiting period). There was no significant differences between groups regarding baseline characteristics, echocardiographic and procedure data. There were no significant differences between both groups regarding the first-pass PV isolation (P=0.49) and the presence of low voltage areas (P=0.71). Median PVI time (P=0.40), median fluoroscopy time (P=0.35) and median overall procedure time (P=0.70) were also similar between groups. The acute PVR rate was similar between both groups (8.2% for the waiting period group vs 11.1% in the group without a waiting phase, P=0.40). After a median follow-up of 14 (IQR 12–18) months, there was no significant difference on the arrhythmia recurrence between groups (4.9% for the waiting group vs 12.7% for the group without a waiting phase, P=0.13). Both groups presented a similar arrhythmia freedom over time (log rank P of 0.109). The waiting period time was not a predictor of recurrence during follow-up (p=0.13). Conclusion: PVI guided by Ablation Index preclude the need of a waiting phase. Adding a 20-minute waiting period did not significantly increase the acute PV reconnection, neither improve the 1-year arrhythmia freedom. Funding Acknowledgement: Type of funding sources: None.